Channels of transmission of inequality to growth: A survey of the theory and evidence from a Portuguese perspective - Duarte, Adelaide (2009)
We review the theoretical and empirical literature on the relationship between inequality and economic growth from the perspective of the Portuguese economy in order to identify the correct (predicted) sign for the relationship in this particular country and the underlying mechanisms that explain it. Different mechanisms relating inequality and economic growth can be at stake explaining why different countries can experience different outcomes in the same period of time or why the same country experiences different outcomes in different periods of time. It is thus fundamental to correctly identify the channels of transmission of inequality to growth in the Portuguese economy. Ideally, all the mechanisms selected should be tested, but prior judgments should also lead us to produce a ranking of the mechanisms according to its relevance for the economy under analysis. This correct identification and ranking leads to more accurate policy recommendations as far as redistributive policies for the Portuguese economy are concerned.